PARA-AORTIC LN INVOLVED DYSGERMINOMA MASQUERADING AS MYOMA DURING PREGNANCY: CASE STUDY - Lee, Eun hyun; Ji, Yong-Il (International Journal of Research -GRANTHAALAYAH, 2018)
Ovarian dysgerminoma is a malignant germ cell tumor and it account for 1-5% of all ovarian cancers. Dysgerminoma usually occurs in adolescence and early adult life. So, it could cause problems in fertility and if it is diagnosed during pregnancy, feto-maternal problems will be incurred. Hereby, we report a case of successful delivery associated with para-aortic Lymph Node (LN) involved ovarian dysgerminoma masquerading as myoma during pregnancy and recommend ultrasound guided fine needle aspiration cytology for ovarian masses should be considered.